Effectiveness of tricalcium silicate-based cements: Systematic review and meta-analysis - Gaia D'Amico; Susana Muwaquet Rodriguez (Elsevier, 2024)
Introduction: Tricalcium silicate-based cements exhibit several beneficial properties for dental health and biocompatibility, which can induce biomineralisation. Objectives: To assess the sealing ability and intratubular penetration of tricalcium silicate-based sealers using warm and cold obturation techniques. Materials and Methods: An electronic search was conducted in PubMed, Scopus, and Web of Science databases for endodontically treated teeth with bioceramics and their sealing capacity in root canal obturation published up to February 2023. Results: Of the 90 articles, 16 met the inclusion criteria, and only 10 were used for the meta-analysis, of which four addressed intratubular penetration, four addressed sealing capacity, and two addressed both variables. In the sealing capacity group, the meta-analysis concluded a standardised mean difference (SMD) of −1.31 in favour of the test group (warm) with a certain nonsignificant trend (p = 0.081); regarding intratubular penetration, the meta-analysis concluded an SMD = 2.34 in favour of the test group (warm) with significantly greater penetration (p = 0.032). Conclusion: The warm obturation technique introduced significantly greater intratubular penetration than the cold technique, along with a remarkably superior sealing capacity compared to the cold technique, approaching statistical significance.